2004
DOI: 10.1108/02686900410524382
|View full text |Cite
|
Sign up to set email alerts
|

Internal auditors’ role and authority

Abstract: In this study, internal auditors are asked to come to a view on whether functions they perform in connection with internal audit engagements are essential, and to what degree. Inspired by Burns, Greenspan and Hartwell’s concept of the true professional, there is an underlying interest in determining whether, and under what circumstances, internal auditors’ enjoy the authority over and independence from management that we might expect of a professional. The findings emerge from a survey of New Zealand auditors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 14 publications
4
36
1
2
Order By: Relevance
“…Regarding Hypothesis (1), the result of employees' sample is consistent with many studies (Van Peursem, 2004;Mihret and Yismaw, 2007;Intakhan and Ussahawanitchakit, 2010) and supported by IIA (1999) internal audit definition, and Moeller (2009) who associates internal audit effectiveness with the significant business activities, developments, voluminous and diverse transactions' results. Hypotheses (1) is accepted for employees' sample but not for managers one.…”
Section: Internal Audit Effectiveness and Audit Scopesupporting
confidence: 73%
See 2 more Smart Citations
“…Regarding Hypothesis (1), the result of employees' sample is consistent with many studies (Van Peursem, 2004;Mihret and Yismaw, 2007;Intakhan and Ussahawanitchakit, 2010) and supported by IIA (1999) internal audit definition, and Moeller (2009) who associates internal audit effectiveness with the significant business activities, developments, voluminous and diverse transactions' results. Hypotheses (1) is accepted for employees' sample but not for managers one.…”
Section: Internal Audit Effectiveness and Audit Scopesupporting
confidence: 73%
“…Van Peursem (2004) found out that the internal auditors are highly associated with the management which in turn can threaten their independency. Sarens and de Beelde (2006) examined this association for five Belgian companies and they found a lack in objectivity and weak association with auditing committee when internal auditors operate in managements support role.…”
Section: Internal Audit Effectiveness and Management's Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Burns et al (1994) raise concerns about the internal auditor's real level of authority, and in particular over the mystique auditors enjoy and the cruciality with which their role is viewed by others. An earlier survey (Van Peursem, 2004) revealed that New Zealand internal auditors do not enjoy the clear level of mystique or cruciality that mark true professions. Without such influence, the internal auditor may not be in a position to influence management when management's actions are inappropriate, and they may not be heard by, or influence, those in governance to the degree needed.…”
Section: Introductionmentioning
confidence: 99%
“…Competences typically involve the development of specialist expertise.From audit perspectives; the auditors' competencies can also increase the effectiveness of the IAQ team by improving the recognition of their role within the organization. Previous studies underlined that line managers often believe that internal auditors do not have enough knowledge to provide useful help (Griffiths, 1999;Van Peursem, 2004 and, if this is the case, they do not take into account their advice, hence reducing the effectiveness of IAQ (Van Peursem, 2004). …”
Section: Auditor Competenciesmentioning
confidence: 99%